MODEL BIMBINGAN (GUIDANCE) UNTUK PEMBERDAYAAN CAREGIVER (PENGASUH) LANSIA DI TATANAN KELUARGA - Nur Iszakiyah,; Nindawi, Nindawi; Endang FS,; Taufiqur Rahman,; Prastomo Suhendro,; Anggeria Oktavisa Denta,; Isnaini Novita Sari,; Rahayu Yuliana W, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Elderly (elderly) is a life journey when humans enter the final stage of their life phase. The elderly are often also called the beginning of the end. Currently, this age group is increasing in number. The population pyramid that used to be pointed at the top is now getting wider at the top. For the elderly group, starting from pre-elderly, they will experience a completely different situation. Although the spirit is still burning, health and physical fitness begin to decline and are very noticeable when they reach the age of 60 years. Physical health and fitness, mental spirituality and memory, need to be maintained. The Covid-19 pandemic is a storm that has hit humans. Covid-19 is not the first pandemic-causing disease in the world. Unlike a pandemic, the spread of disease can also be in the form of endemics, namely diseases that continue to spread in a certain area and do not spread quickly to other areas. If a disease spreads quickly to other areas, then the spread of the disease is called an epidemic. Returning to Covid-19, this virus is very prone to attacking the elderly quickly and has a high mortality rate. The purpose of this community service is to empower elderly caregivers in the family setting and identify the effectiveness of the guidance model by caregivers. In 2019, the number of elderly people in Indonesia was 9.7% of the total population, or around 25.9 million people. It is estimated that in 2035 it will be 48 million people (15.77%). The elderly group is not only increasing in number but also increasing in life expectancy. The number of participants was 30 people. The methods used were discussion, demonstration, skills training and skills evaluation. The results of the training for caregivers showed an increase in knowledge based on pre-test and post-test scores. There was an increase in skills seen from four skills, namely communication in the elderly, active movement, passive movement, mobilization, and daily activity training. Activities related to improving caregivers' abilities in caring for the elderly who experience daily problems related to psychological approaches. It is recommended that community service in health institutions can be carried out periodically, and lecturers can improve their innovation so that they can contribute to the health of the elderly.